Ciplukan (Physalis angulata L.): Review Tanaman Liar yang Berpotensi Sebagai Tanaman Obat - Fadhli, Haiyul; Ruska, Shinta Liana; Furi, Mustika; Suhery, Wira Noviana; Susanti, Emma; Nasution, Musyirna Rahmah (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Ciplukan (Physalis angulata L.) has been widely used as a traditional medicine in several countries and regions in Indonesia, such as to increase blood flow and relieve body aches, asthma, diabetes, chickenpox, cough medicine, fever, diarrhea, hypertension, and back pain. This article reviews the potential of ciplukan to overcome various health problems. The preparation of this review article uses references from research articles related to the results of phytochemical screening, the isolation of secondary metabolites, and biological activity tests (pharmacology) of Physalis angulata plants reported in the last 10 (ten) years. This plant contains many secondary metabolite compounds isolated from its roots, leaves, stems, and fruits, such as physalin, withanolide, and flavonoid glycoside compounds. Several studies have reported that this plant has biological and pharmacological activities such as antioxidants, toxicity, anticancer, anti-inflammatory, antidiabetic, antidiarrheal, antibacterial, antifibrotic, and anti-hypercholesterolemia.